Speculative Fiction in Russia and the Alchemy of Renewal. (1st October 2016) - Vladimirskii, Vasilii
Abstract : Vasilii Vladimirskii takes science fiction in Russia as an example of how genre fiction can evolve and remain attractive to readers. The article outlines the history of Anglophone science fiction through several phases of evolution but argues that literary conditions in the Soviet Union did not favor the growth of a tenacious literary opposition in science fiction. Vladimirskii is pessimistic about the possibility that speculative fiction in Russia can renew itself by selecting the best marginal works, because the mainstream so dominates that part of the literary market.